ANALYSIS OF TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) ABILITY OF PROSPECTIVE ACCOUNTING TEACHER STUDENTS - Pratiwi, Nova; Sutarni, Nani; Dahlan, Dadang (Jurnal Pendidikan Ilmu Sosial, 2025)
This study aims to investigate Prospective Accounting teachers' Technological Pedagogical and Content Knowledge (TPACK) abilities. The population of this study was 133 Accounting Education students of Universitas PGRI Palembang in the academic year 2023/2024, with a sample of 70 students taken through purposive sampling. This descriptive quantitative research measured 7 TPACK indicators using a 29-item questionnaire. The data were analyzed using descriptive statistics (percentage) and converted to qualitative categories of TPACK ability. The findings showed that the TPACK ability of prospective accounting teachers was in a good category. The indicators with the highest mean scores were Technological Content Knowledge (TCK) and Technological Knowledge (TK). In contrast, the indicators with the lowest mean scores were Pedagogical Knowledge (PK) and Pedagogical Content Knowledge (PCK). The implications of this study emphasize the importance of improving TPACK skills, especially in the PK and PCK components, through optimizing lectures in educational courses through increasing the portion of teaching practices, such as simulations, micro-teaching, and lesson study, as well as training that focuses on classroom management and technology-based learning design. Improving TPACK skills will prepare future accounting educators to integrate technology, pedagogy, and content effectively in learning.